Pengaruh Kompensasi Terhadap Kinerja Guru Honorer di Sekolah Dasar Kecamatan Somba Opu Kabupaten Gowa - Airil Anwar; Burhanuddin Burhanuddin; Zainal Ruma (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
It is important for schools to consider the inclusion of honorary teaching staff to expedite the process of paying them salaries. Apart from that, the government is also obliged to prioritize providing assistance to schools experiencing a shortage of civil servant teachers, because there are still many institutions that need additional teaching staff. This research uses quantitative research methods, with the main focus on producing numerical data. The data collection process involves conducting field research, which involves gathering information directly from participants and observing their behavior directly. The findings of this research show that compensation has a significant role in shaping the performance of Honorary Elementary School Teachers in Somba Opu District, Gowa Regency. It was found that approximately 28.4% of the variation in performance could be attributed to compensation, demonstrating the importance of compensation in determining teacher effectiveness. This shows that the amount of compensation received by honorary teachers in Somba Opu District, Gowa Regency has a direct impact on their level of performance.